Prospective Study about the Utility of Endoscopic Ultrasound for Predicting the Safety of Endoscopic Submucosal Dissection in Early Gastric Cancer (T-HOPE 0801) - Daisuke Kikuchi; Toshiro Iizuka; Shu Hoteya; Akihiro Yamada; Tsukasa Furuhata; Satoshi Yamashita; Kaoru Domon; Masanori Nakamura; Akira Matsui; Toshifumi Mitani; Osamu Ogawa; Mitsuru Kaise (Gastroenterology Research and Practice)
Background. Intraoperative bleeding is an important determinant for safety of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC). This study aimed to prospectively evaluate the usefulness of endoscopic ultrasound (EUS) for predicting ESD safety. Methods. A total of 110 patients with EGC were divided into two groups based on EUS findings: group P, almost no blood vessels in submucosa, or ≤4 small vessels per field of view; group R, remaining patients. Primary endpoint was the decrease in Hb after ESD. Secondary endpoints included procedure time and the incidence of muscle injury and clip use. Results. A total of 89 patients were evaluated. Fifty were classified into group P and 39 into group R. Mean decrease in Hb was 0.27 g/dL in group P and 0.35 g/dL in group R, with no significant difference. Mean procedure time was significantly longer in group R (105.4 min) than in group P (65.5 min) (P<0.001). The incidence of muscle injury and clip use were significantly higher in group R (25.6%/48.7%) than in group P (8.0%/20.0%) (P=0.02/P=0.004). Conclusion. Preoperative EUS can predict procedure time and the incidence of muscle injury and clip use and is thus considered useful for predicting gastric ESD safety.